2008
DOI: 10.1021/om800574s
|View full text |Cite
|
Sign up to set email alerts
|

Competing Germene and Germylene Extrusion from Photolysis of 1,1-Diarylgermacyclobutanes. Substituent Effects on Germene Reactivity

Abstract: Direct irradiation of 1,1-diphenyl-, 1,1-bis[4-(trifluoromethyl)phenyl]-, and 1,1-bis[3,5-bis(trifluoromethyl)phenyl]germacyclobutanes (2, 4, and 5, respectively) in methanolic C6D12 solution affords products consistent with the competing formation of the corresponding 1,1-diarylgermenes and diarylgermylenes, along with ethylene and cyclopropane. The relative yields of the two Ge-containing primary products (germene:germylene) vary with the extent of CF3 substitution on the aryl rings, decreasing in the order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 46 publications
2
16
0
Order By: Relevance
“…[13]). 64 We anticipated that GePh 2 should be detectable from 17 under these conditions since its co-product (cyclopropane) is inert; we have previously shown that the photolysis of 6a in low-temperature glasses does not afford Table 2. Second-order rate constants for the reactions of CCl4 with germylenes 8a-8f and digermenes 9a-9g in deoxygenated hexanes solution and with the corresponding germylene-THF complexes in THF at 25 8C.…”
Section: Low-temperature Spectroscopic Studiesmentioning
confidence: 98%
See 1 more Smart Citation
“…[13]). 64 We anticipated that GePh 2 should be detectable from 17 under these conditions since its co-product (cyclopropane) is inert; we have previously shown that the photolysis of 6a in low-temperature glasses does not afford Table 2. Second-order rate constants for the reactions of CCl4 with germylenes 8a-8f and digermenes 9a-9g in deoxygenated hexanes solution and with the corresponding germylene-THF complexes in THF at 25 8C.…”
Section: Low-temperature Spectroscopic Studiesmentioning
confidence: 98%
“…4a). The absorption at 326 nm is assigned to germene 18, 64,67 whereas the 460 nm absorption band is assigned to GePh 2 . The latter spectrum agrees well with those obtained in low-temperature experiments using other precursors, such as the known disilylgermane 19 26,68 and disilyldigermane 20.…”
Section: Low-temperature Spectroscopic Studiesmentioning
confidence: 99%
“…For the synthesis of the title compound, see: Leigh et al (2008). For related compounds see: Tokitoh et al (1995); Eichler et al (1999); Meiners et al (2002); Tajima et al (2005).…”
Section: Related Literaturementioning
confidence: 99%
“…Photolysis of 1,1-diarylgermetanes results in two competing modes of cycloreversion: (2 + 2) to yield the corresponding 1,1-diarylgermene (R 2 Ge=CH 2 ) and ethylene, and (3 + 1) to yield the corresponding diarylgermylene (R 2 Ge) and cyclopropane (Leigh et al, 2008). While the quantum yield for decomposition of the germetane remains roughly constant regardless of aromatic substitutent (Φ ca 0.10), decreasing the electron density at germanium by aromatic ring substitution favors formation of the germylene and cyclopropane (Leigh et al, 2008). The molecular structure of (I) is shown in Figure 1.…”
Section: S1 Commentmentioning
confidence: 99%
See 1 more Smart Citation